Detection of gaseous dimethylamine using vocus proton-transfer-reaction time-of-flight mass spectrometry. (15th December 2020) - Wang, Yuwei; Yang, Gan; Lu, Yiqun; Liu, Yiliang; Chen, Jianmin; Wang, Lin
Abstract: The newly developed Vocus proton-transfer-reaction time-of-flight mass spectrometer (Vocus PTR-TOF) is able to simultaneously detect hundreds of gaseous compounds including a big fraction of volatile organic compounds (VOCs) with outstanding mass resolution and sensitivity. Here, we present an application of Vocus PTR-TOF to monitor gaseous dimethylamine (DMA). The sensitivity towards DMA was improved by tuning the voltage settings of the segmented quadrupole following the molecular ion reactor to obtain a suitable ion transmission window. With the assistance of a permeation tube calibration method, the sensitivity of Vocus PTR-TOF for DMA detection was 2.68 cps pptv −1 at a TOF extraction frequency of 16 kHz and the detection limit was 1.44 pptv at 3σ of the background signal for a 1 min integration time. Laboratory experiments at a series of controlled relative humidity (RH) show that RH of the sample had little influences on the measurement of DMA. Vocus PTR-TOF with this hardware setup was deployed from December 2018 to January 2019 at Wangdu, Hebei Province, China. The temporal profile of C2 -amines with a high time resolution was obtained, while the detection of VOCs remained successful. Such simultaneous measurements of these compounds are meaningful as these compounds are all relevant to aerosol nucleation and growth. Our results indicate that Vocus PTR-TOF can be a powerful tool in both field and laboratory studies for new particle formation research.